Spontaneous pneumomediastinum in a young male secondary to chronic marijuana abuse - Samanta, Palash; Romero, Mahiry Salinas; Roper, Jon; Amin, Hossam (Eastern Journal of Medical Sciences, 2017)
Illicit drug use is emerging as a global health problem, also leading to deteriorated socioeconomic condition. Cannabis (Marijuana) is used throughout the world, and its use is increasing. Marijuana is associated with airway inflammation leading to pneumothorax, pneumomediastinum. It also predisposes to lung cancer. Here, we are presenting a young male presented with a cough and progressively worsening dyspnea. Imaging showed pneumomediastinum. The patient revealed chronic marijuana use for many years. Clinicians treating young adults and adolescents should be aware of the entity associated with illicit drug use, and thorough clinical and social history is warranted for early diagnosis of the perforated organ.